A research methodology workshop on ‘Social issues in use of medicines’ – cooperation between institutions and participant feedback - Shankar, PR; Subish, P; Alam, K (Journal of College of Medical Sciences-Nepal, 2012)
A research methodology workshop on social issues in use of medicines was conducted at Pokhara, Nepal from December 21st to 24th, 2008. The present study was conducted to obtain detailed participant feedback about the workshop and obtain suggestions for improvement. The participants’ knowledge was assessed at the start of the workshop and on the final day by noting their agreement with a set of 40 statements using a modified Likert-type scale. The areas of qualitative research, statistics, research methodology, drug use, pharmacovigilance, journal and general were covered. Certain statements were negative and their scores were reversed. The total score was calculated. The median total scores were compared among various subgroups of respondents. Session evaluation was done at the end of each session. A total of twenty-five participants attended the sessions. The workshop significantly improved the median total scores. Significant improvements were also seen in the subcategories Statistics and Journal. The scores of certain statements were low. The evaluation scores of certain sessions were low. The overall participant opinion about the workshop was positive. Occasional problems with accent of the facilitator and lack of internet access were major problems noted. Some participants felt the workshop was too hectic. Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-1, 60-67 DOI: http://dx.doi.org/10.3126/jcmsn.v8i1.6829